Forearm muscle oxygenation and blood volume parameters during sustained contraction performance in youth sport climbers - Gilic, B.; Feldmann, A.; Vrdoljak, D.; Sekulic, D. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Forearm muscle strength and endurance are essential determinants of sports climbing success. This study aimed to investigate whether delayed rates of muscle oxygen saturation and total hemoglobin correlate to sustained contraction performance of youth climbers. METHODS: Twelve recreational and competitive youth sport climbers (six females, six males) participated in the study. Variables included finger flexors muscle maximal voluntary contraction, sustained contraction test (SCT), muscle oxygen dynamics (SmO2), and blood volume (tHb) parameters. Pearson`s correlation coefficients were calculated to determine the correlation between physiological and performance variables. RESULTS: SCT had a significant positive relationship to SmO2 delayed rate (r=0.728, P=0.007), and a significant negative relationship to tHb delayed rate (r=-0.690, P=0.013). SmO2 delayed rate and tHb delayed rate also had a significant negative correlation (r=-0.760, P=0.004). CONCLUSIONS: According to the results of this study, it can be suggested that delayed rates of SmO2 and tHb could be used in determining and predicting sustainable finger flexors performance in youth climbers. However, future studies investigating delayed rates of SmO2 and tHb in climbers of different ability levels are warranted to investigate this issue in more detail.